An early start at a professional soccer academy is no prerequisite for world cup soccer participation - Platvoet, S.; Heuveln, G. V.; Dijk, J. V.; Stevens, T.; Niet, M. D. (Frontiers in Sports and Active Living, 2023)
Introduction: 829 players from 32 nations on five continents participated in the 2022 men's World Cup tournament in Qatar. Not much is known about the youth careers of World Cup players from all over the world, especially about the age at which they began playing youth soccer in a professional academy. This study aimed to provide insights in the age national team players participating in World Cup Qatar 2022 started playing for a professional soccer academy and whether their starting age relates to continent and their current playing position (i.e., goalkeepers, defenders, midfielders, and forwards).